Impression management, overclaiming, and perceived unethical conduct: The role of male and female managers - Schoderbek, P. P. (Journal of business ethics, 1996)
This study examines the impact of impression management and overclaiming on self-reported ethical conduct of 174 managers (67 male, 107 female) who worked for a large not-for-profit organization. As anticipated, impression management and overclaiming positively influenced perceived unethical conduct of managers. Female managers were more prone to impression management than male managers. There was no significant difference in perceived unethical conduct or level of overclaiming of male and female managers.